Babel's Tower: South Africa's Wikipedias - Graaf, Michael (Department of Computer Science, 2020)
This dissertation is a comparative examination firstly of usage of, and contribution to, the Wikipedias in ten of South Africa’s eleven official languages, and secondly of possible measures to address the situation discovered in the first investigative stage. The historical context is reviewed and it is argued that the number of official languages (and therefore Wikipedias) results from decisions made in colonial and apartheid eras. Public-domain usage and contribution statistics from the Wikimedia Foundation are analysed, revealing poor growth in most cases; possible interventions via both cultural/educational strategies and technological options are reviewed.